2021
DOI: 10.1186/s12902-021-00814-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of serum delta-like ligand-4 level with the severity of diabetic retinopathy

Abstract: Background Diabetic retinopathy (DR) is one of the most serious microvascular complications of type 2 diabetes mellitus (T2DM). Delta-like ligand-4 (DLL4) maintains the normal physiological microenvironment of the retina. However, the relationship between the level of DLL4 and the severity of DR remains unclear. Methods We retrospectively analyzed serum DLL4 levels and other laboratory and clinical data in 94 T2DM patients (35 patients without DR [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(20 reference statements)
0
1
0
1
Order By: Relevance
“…Under HG conditions, blocking Dll4/Notch inhibited neovascularization [ 103 ]. Zhu et al [ 104 ] reported high serum Dll4 levels as a biomarker for diabetic retinopathy. Additionally, in DKD, the Notch pathway activation promoted macrophage polarization [ 105 ].…”
Section: Cellular Crosstalk Of Renal Tecsmentioning
confidence: 99%
“…Under HG conditions, blocking Dll4/Notch inhibited neovascularization [ 103 ]. Zhu et al [ 104 ] reported high serum Dll4 levels as a biomarker for diabetic retinopathy. Additionally, in DKD, the Notch pathway activation promoted macrophage polarization [ 105 ].…”
Section: Cellular Crosstalk Of Renal Tecsmentioning
confidence: 99%
“…Понад 25 % хворих уже мають ранню стадію ДР при початковому діагнозі ЦД, а 60 % хворих із тривалістю ЦД 2-го типу понад 20 років мають ураження очного дна різного ступеня тяжкості [7]. Майже в усіх пацієнтів з діагностованим ЦД 1-го типу протягом двох десятиліть після встановлення діагнозу розвивається ДР; для ЦД 2-го типу ця ймовірність зростала до 80 % через 20 років після початку захворювання, а близько половини пацієнтів з нелікованою ПДР з високою ймовірністю матимуть сліпоту протягом 5 років [8].…”
Section: клінічна офтальмологія / Clinical Ophthalmologyunclassified